APOBEC3C, a nucleolar protein induced by genotoxins, is excluded from DNA damage sites. (4th October 2021) - Constantin, Daniel; Dubuis, Gilles; Conde‐Rubio, María del Carmen; Widmann, Christian
Abstract : The human genome contains 11 APOBEC (apolipoprotein B mRNA editing catalytic polypeptide‐like) cytidine deaminases classified into four families. These proteins function mainly in innate antiviral immunity and can also restrict endogenous retrotransposable element multiplication. The present study focuses on APOBEC3C (A3C), a member of the APOBEC3 subfamily. Some APOBEC3 proteins use their enzymatic activity on genomic DNA, inducing mutations and DNA damage, while other members facilitate DNA repair. Our results show that A3C is highly expressed in cells treated with DNA‐damaging agents. Its expression is regulated by p53. Depletion of A3C slightly decreases proliferation and does not affect DNA repair via homologous recombination or nonhomologous end joining. The A3C interactomes obtained from control cells and cells exposed to the genotoxin etoposide indicated that A3C is a nucleolar protein. This was confirmed by the detection of either endogenous or ectopic A3C in nucleoli. Interestingly, we show that A3C is excluded from areas of DNA breaks in live cells. Our data also indicate that the C‐terminal part of A3C is responsible for its nucleolar localization and exclusion from DNA damage sites. Abstract : APOBEC3C, via its C‐terminal domain, is targeted to nucleoli and actively excluded from DNA nuclear lesion sites. Its expression is stimulated by genotoxins in a p53‐dependent manner, but APOBEC3C is expendable for double‐stranded DNA repair.